Universal data model for the formation of the critical information infrastructure of the state objects list - Гнатюк, Сергій Олександрович; Сидоренко, Вікторія Миколаївна; Сєйлова, Нургуль Абадуллаєвна (Ukrainian Scientific Journal of Information Security, 2017)
In recent times all over the world the number of different emergency situations was increased. Every day mass media informs about natural and man-caused disasters, weapon conflicts, acts of terrorism, global crimes, acts of piracy that were committed by both crime organizations and single offenders. Increasingly frequently as a result of these events many people falls a victim and also state critical importance systems and resources can be damaged. By this means most of world leader states have attended to methods and means of identifying, systematization and security assurance for critical infrastructure objects. Loss or operational breakdown of these objects can cause significant or irreparably damage for national security of the state. However, as shown by the analysis of the domestic normative base, today in Ukraine an exhaustive list of objects of the critical information infrastructure of the state is not yet formed and there is no clear mechanism for the formation of this list. Given the above, the paper proposes a universal data model for the formation of critical information infrastructure of the state objects list and, on the basis of the developed model, a list of critical objects in the field of civil aviation is formed. In further works is planned to develop efficient methods and tools for identifying and ranking objects, the list of which is formed using the proposed model of data.